2021
DOI: 10.1029/2020wr027829
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of CO2 Density‐Driven Flow in Carbonate Aquifers: Effects of Dispersion and Geochemistry

Abstract: • Effect of hydrodynamic dispersion is studied on the dynamics of CO 2 convection. • Dynamics of convective mixing in carbonate aquifers is simulated by reactive transport modelling. • Chemical reactions have non-monotonic effects on carbon storage before and after convection 10 onset. 11 • The importance of realistic geochemical modelling and different reaction pathways subsequent 12 to plume propagation is shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 106 publications
(239 reference statements)
1
14
0
Order By: Relevance
“…In effect, many of the aforementioned numerical studies (either 2D or 3D) have considered simple diffusive transport, either because considering only molecular diffusion allows for analytical developments otherwise intractable, or because they considered a Péclet number sufficiently small for the impact of dispersion to always be negligible with respect to that of molecular diffusion (this hypothesis being in any case reasonable at the initiation of the instability). In particular, to our knowledge, those among the 3D numerical studies which have accounted for hydrodynamic dispersion have not investigated its effect in detail, but have rather focused on the effect of carbonate geochemical reactions 25 . Furthermore, while the nonlinear onset time is known from numerical and experimental studies alike to decrease with the Rayleigh number 2,4,5,12 , the literature has reported conflicting views regarding the influence of hydrodynamic dispersion on the onset of 4 This is the author's peer reviewed, accepted manuscript.…”
Section: Accepted To Phys Fluids 101063/50086370mentioning
confidence: 99%
“…In effect, many of the aforementioned numerical studies (either 2D or 3D) have considered simple diffusive transport, either because considering only molecular diffusion allows for analytical developments otherwise intractable, or because they considered a Péclet number sufficiently small for the impact of dispersion to always be negligible with respect to that of molecular diffusion (this hypothesis being in any case reasonable at the initiation of the instability). In particular, to our knowledge, those among the 3D numerical studies which have accounted for hydrodynamic dispersion have not investigated its effect in detail, but have rather focused on the effect of carbonate geochemical reactions 25 . Furthermore, while the nonlinear onset time is known from numerical and experimental studies alike to decrease with the Rayleigh number 2,4,5,12 , the literature has reported conflicting views regarding the influence of hydrodynamic dispersion on the onset of 4 This is the author's peer reviewed, accepted manuscript.…”
Section: Accepted To Phys Fluids 101063/50086370mentioning
confidence: 99%
“…Erfani et al. (2021) show that CO 2 density‐driven flow in carbonate aquifers should not be viewed as an isolated processes but rather strongly coupled to geochemical processes that have significant impact on the convection processes. This holds a fortiori in karst aquifers and karstification where the coupling of flow with reaction drives the genesis and growth of conduits or caves on even longer time scales.…”
Section: Introductionmentioning
confidence: 99%
“…3 , often summarized as total inorganic carbon (TIC) have impact on the water density. As in Erfani et al (2021), the effect of dissolved ions on water density is aggravated also in karst systems, when for example, Ca ++ ions are considered and vertically oriented fingering regimes are likely to receive further stimulation close to reactive carbonate surfaces.…”
mentioning
confidence: 97%
“…Solute transport in porous media is relevant to a wide range of applications in contaminant hydrogeology, geothermal engineering, petroleum engineering, and a variety of chemical engineering systems (Whitaker 1967;Fried and Combarnous 1971;Balakotaiah et al 1995;Coats and Smith 1964;Erfani et al 2019Erfani et al , 2020Erfani et al , 2021. Transport in porous materials is controlled by two physical processes: advection and diffusion.…”
Section: Introductionmentioning
confidence: 99%